2022
DOI: 10.1038/s41598-022-19170-z
|View full text |Cite
|
Sign up to set email alerts
|

Quantum Zeno repeaters

Abstract: Quantum repeaters pave the way for long-distance quantum communications and quantum Internet, and the idea of quantum repeaters is based on entanglement swapping which requires the implementation of controlled quantum gates. Frequently measuring a quantum system affects its dynamics which is known as the quantum Zeno effect (QZE). Beyond slowing down its evolution, QZE can be used to control the dynamics of a quantum system by introducing a carefully designed set of operations between measurements. Here, we pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 59 publications
0
7
0
Order By: Relevance
“…Ozaydin et al recently showed that BE activation of Horodecki et al [12] can be realized via QZD without requiring difficult to implement three-level controlled gates [33]. Bayrakci and Ozaydin have designed a QZD-based entanglement swapping protocol and extended it to realize quantum repeaters for long-distance quantum communications [34].…”
Section: Quantum Zeno Dynamicsmentioning
confidence: 99%
See 1 more Smart Citation
“…Ozaydin et al recently showed that BE activation of Horodecki et al [12] can be realized via QZD without requiring difficult to implement three-level controlled gates [33]. Bayrakci and Ozaydin have designed a QZD-based entanglement swapping protocol and extended it to realize quantum repeaters for long-distance quantum communications [34].…”
Section: Quantum Zeno Dynamicsmentioning
confidence: 99%
“…Similar to the QZD procedure in [32][33][34], as the QZD iterations start, the initially separated two-qubit systems become entangled. Because the initially separated qubits held by parties (nodes of the quantum network) Alice, Bob, and Charlie are entangled to qubits in other nodes, as shown in Figure 1a, implementing the local QZD on their initially separable qubits and entangling them, all the eight qubits in the network are entangled without performing teleportation or Bell measurements.…”
Section: Rotate-measure Operation For Qzdmentioning
confidence: 99%
“…The probability E P that the system will be found to be in an error state corresponding to one of the last two terms in equation ( 13) is given by 22 .…”
Section:  mentioning
confidence: 99%
“…The Zeno effect has been experimentally demonstrated using 9 Be + ground-state hyperfine levels 14 , Bose-Einstein condensates 15 , ion traps 16 , nuclear magnetic resonance 17 , cold atoms 18 , cavity QED 19 , and large atomic systems 13 . It has also been shown that the Zeno effect is a sufficient resource for the implementation of quantum logic gates 20,21 , which could be used as the basis of a quantum computer 21 or quantum repeaters 22 . The Zeno effect can also be used to prepare various nonclassical or entangled states [23][24][25][26][27] and to protect entanglement once it has been generated 28,29 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation